(untitled) (Research, Society and Development, 2021)
The objective was: to evaluate the behavior of dengue in times of pandemic of COVID-19 in the state of Piauí. As a methodological design; the research is characterized as an epidemiological, descriptive retrospective study, carried out based on data from the health department of the state of Piauí (SESAPI) and compared using the data available on the DATASUS platform. Thus, since it is a study with public databases, it did not need to be submitted to the CEP of the proposing institution or the offer of IC. The retrospective cut was made from the confrontation of notifications of dengue cases in the years 2019/2020. Results and discussion; during 2019 the state notified a total of 8,015 cases, confirming a total of 6,762. in 2020, the state notified a total of 2,198, and 1,855 cases were confirmed. Presenting a reduction of 72.9% of the cases in relation to the same periodicity. In relation to the number of notifying municipalities in 2019, there were: 170 municipalities and, in 2020, that number was 118 notifying municipalities. Presenting a reduction of 52 municipalities. It is worth mentioning that it is not possible to state clearly the real reason for this reduction, if motivated by the lack of users’ demand for health services and / or if they are caused by the application of individual preventive measures, since in times of pandemic, people have become more time at home. Conclusion: there is a notable reduction in the reduction of dengue cases in the state of Piauí, during the first year of the COVID-19 pandemic in the state.